A study of employee perception of internal CSR and employee commitment in VNPT Technology Company - Trần, Thế Hùng (2020)
The research determineswhether have a relation between perception of employee about internalCSR and commitment of employeeat VNPT Technology Company. This studydevelop and proposed a theoretical framework for analyzing the relationship between perception of employee of internalCSR and the organizational commitment inFigure 1.In this research, it is aimed to create a model that identifies the connection between perception of employee about internal CSR, and commitment of employee of company